Experimental Researches On Fluorescence Of Aesthetic Dental Coronar Restorations - Bohnert M.; Pollack S.; Witwoski S.; Neumann C.P.P.; Diana Diaconu; Maria-Antonela Beldiman; Simona Stoleriu; Andrian S. (Romanian Journal of Oral Rehabilitation, 2009)
Introduction. The aesthetic dental coronary restorations are made-up by composite resins, compomers or non-metallic prostheses. Natural teeth are fluorescent, and so, the biomaterials used today are fluorescent, too. The determination of fluorescence for coronary restorations is useful in dental medicine and forensic medicine. Material and method. On a black cast of a maxillary arch there have been applied coronary restorations and fixed prostheses from some biomaterials frequently used today: Compafill A 1, Compafill C 3 (Wilde Dental, Germany), CeramX, Dyract extra, Quixfill (Dentsply DeTrey, Germany), Coltene (Whaledent, Germany), Degufill (Degussa, Germany), Concise (3M, USA), Superpont (Spofa Dental, Czech R.), Vita Akzent “sun kiss” ceramic material (Vita ZF., Germany). The fluorescence of these restorations was revealed in photos by the time of UV-A irradiations, than, the photos were comparatively examined from the point of view of intensity and fluorescence chromatics. Using the photometer appliance (fluorescent-photometer) assisted by a computer, realized by Professor Dr. Michael Bohnert, it was measured and graphic registered, the light-length and the intensity of light emitted on UV-A irradiation, thus, the fluorescence of each restoration from the black cast. Results. For each restoration made from such biomaterials, it was observed a particular fluorescence, characteristic. This characteristic was attested also by computerized determination of fluorescence reflected in specific curves. Discussions. In dental medicine, especially in dental prosthetics, it is necessary that restorations and fixed dental prostheses to have the same fluorescence as natural teeth. In forensic medicine, the specific fluorescence can offer an extra element to identify the unidentified bodies. Conclusions. The coronary dental restorations and fixed prostheses present a different fluorescence, corresponding to the biomaterial used. When there are used non-fluorescent biomaterials, they appear with a clear different chromatic aspect from natural teeth, in UV-radiation light, natural light and artificial light.